2010
DOI: 10.2138/am.2010.3607
|View full text |Cite
|
Sign up to set email alerts
|

Natrolite may not be a "soda-stone" anymore: Structural study of fully K-, Rb-, and Cs-exchanged natrolite

Abstract: Since its first discovery in nature, natrolite has been largely known as a sodium aluminosilicate zeolite, showing very limited preference toward cation exchange. Here we show that fully K-exchanged natrolite can be prepared from natural Na-natrolite under mild aqueous conditions and used to subsequently produce Rb-and Cs-exchanged natrolites. These cation-exchanged natrolites exhibit successive volume expansions by ca. 10, 15.7, and 18.5% for K-, Rb-, and Cs-forms, respectively, compared to the original Na-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 22 publications
7
82
0
Order By: Relevance
“…This may result from a little structural changes. Similar changes was described in the case of natrolite exhanged with Rb and Cs [15]. …”
Section: X-ray Powder Diffractionsupporting
confidence: 78%
“…This may result from a little structural changes. Similar changes was described in the case of natrolite exhanged with Rb and Cs [15]. …”
Section: X-ray Powder Diffractionsupporting
confidence: 78%
“…[9] It has recently been shown that various alkali, alkaline-earth, and heavy-metal cations can be exchanged into the natrolite channels, and that the unit cell volume and channel ellipticity of ion-exchanged natrolites have a nearly linear dependence on the cation radius. [4,5] The larger the cation, the less elliptical the channel becomes, and hence, the unit cell volume expands by up to 25 % in the alkali metal series. For example, from Lito Cs-natrolite, the chain rotation angle and unit cell volume vary from 25.58 and 2118.5 3 to 2.98 and 2658.8 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, EFCs and water molecules in Li + -, Na + -, Ca 2 + -, Ag + -, and Sr 2 + -exchanged natrolites (r < 1.3 ) are ordered and distributed over well-separated sites with full site occupancies, [5] whereas those in K + -, Rb + -, and Cs + -exchanged natrolites (r > 1.3 ) reveal statistically disordered arrangements over closely separated sites. [4] The overall symmetry of the ordered cation forms is then dictated by the type of cation. Thus, all the alkaline-earth forms studied so far (Ca 2 + -, Sr 2 + -, and Ba 2 + -exchanged natrolites) adopt a scolecite-like structure in space group Cc, whereas the alkali and heavymetal forms (Li + -, Na + -, Cd 2 + -, Ag + -, and Pb 2 + -exchanged natrolites) crystallize in the original natrolite-like structure in space group Fdd2 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations